Using GIS to Advance Social Economics Research: Geocoding, Aggregation, and Spatial Thinking. Issue 4 (2nd October 2021) - Wilson, Benjamin; Wilson, Neal; Martin, Sierra
Abstract: The political, social, and economic conditions which lead to inequality, poverty, and health disparities have distinct spatial footprints. Geographic information systems (GIS) are a collection of tools that can aid the social economist in the investigation of such phenomena. Geocoding is a technical procedure that matches attribute data to spatial features in GIS. This analysis of social economy discusses the possibilities of spatial analysis and the technical process of geocoding. Using 15 years of address level pediatric data from a local children's hospital, a novel iterative geocoding process is applied for the purpose of investigating the relationship between household environments and health outcomes. This procedure adheres to traditional standards for geocoding (positional accuracy, completeness, and repeatability) while producing multiple spatial data sets that can be associated with a range of environmental and socioeconomic variables related to human health. Describing this technical procedure contributes to a growing methodological toolbox for applying GIS to research in social economics.